THE ERA OF NEUROSYNAPTICS: NEUROMORPHIC CHIPS AND ARCHITECTURE - Agarwal, Siddhartha; Rastogi, Divyanshi; Singhal, Aayush (European Scientific Journal, ESJ, 2015)
Since its invention the modern day computer has shown a significant improvement in its performance and storage capacity.However, most of the current processor cores remain sequential in nature which limit the speed of computation. IBM has been consistently working over this and with the launching of neurosynaptic chips, it has opened a new gateway of thought process. This paper aims at reviewing the various stages and researches that have been instrumental in the overall development of neuromorphic architecture which aims at developing flexible brain like structure capable of performing wide range of real time computations while keeping ultra-low power consumption and size factor in mind. Inspired by the human brain, which is capable of performing complex tasks rapidly and accurately without being programmed and utilizing very less energy, TrueNorth chips tends to mimic the human brain so as to perform complex computations at a faster pace. This has inspired a new field of study aimed at development of the cognitive computing systems that could potentially emulate the brain’s computing efficiency, size and power.The paper also aims to highlight the inadvertent challenges of neuromorphic architecture as posed by the prevailing technologies which are a major field of research in near future.